Fish immunity against nervous necrosis virus (NNV) infection: a review - Roslan, Irfan Hakimi; Abdullah, Azila; Mansor, Nur Nazifah; Nawi, Mohd Firdaus; Abdul Rahim, Amalin Sofea; Mohd Khalid, Hazreen Nita (International Society of Academicians, 2025)
Fish are unique organisms fitted with a certain degree of immune system that are similar to mammals; consists of innate and adaptive immunity. Innate immunity comprised of non-specific cellular and the nonspecific humoral components while adaptive immunity consists of specialized systemic cells and mechanisms that are categorized into two main groups: the humoral and cellular components. In response to nervous necrosis virus (NNV) infection, both innate and adaptive immunity mechanisms play crucial roles. NNV invasion in fish triggers phagocytosis by antigen-presenting cells (APCs). These cells process viral proteins into peptide fragments, presenting them on major histocompatibility complex (MHC) class II molecules, a crucial protein component that initiate specific adaptive immune response against NNV infection. This will eventually activate adaptive immunity pathway to stimulate the proliferation and maturation of the B cells. As B cells matured, antibodies will be produced to suppress the pathogen through series of process known as opsonization and neutralization before phagocytosis takes place. Following secondary exposure with the same antigen, B cells will rapidly proliferate, releasing significant number of antibodies to fight the antigen. Overall, this review elucidates the complex interplay between innate and adaptive immune responses in fish, highlighting their crucial roles in combating NNV infection through mechanisms such as phagocytosis, antigen presentation, and antibody production.